2013
DOI: 10.1007/s10571-013-9958-z
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic Acid B Induces Apoptosis in Human Glioma U87 Cells Through p38-Mediated ROS Generation

Abstract: Salvianolic acid B (SalB), the main water-soluble bioactive compounds isolated from the traditional Chinese medical herb Danshen, has been shown to exert anti-cancer effect in several cancer cell lines. The aim of our study was to investigate the potential anti-cancer effect of SalB in human glioma U87 cells. We found that treatment with SalB significantly decreased cell viability of U87 cells in a dose- and time-dependent manner. SalB also enhanced the intracellular ROS generation and induced apoptotic cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 24 publications
1
47
0
Order By: Relevance
“…[38][39][40][41] However, some studies demonstrated contrary views. [42][43][44] The different regulation networks may cause varied biological effects in diverse cells and organisms. To elucidate the specific relationship between ROS and p38, we checked the effect of NAC and SB202190, selective inhibitors of ROS and p38, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41] However, some studies demonstrated contrary views. [42][43][44] The different regulation networks may cause varied biological effects in diverse cells and organisms. To elucidate the specific relationship between ROS and p38, we checked the effect of NAC and SB202190, selective inhibitors of ROS and p38, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, extracellular signal-regulated kinase (ERK)1/2, as another transduction factor of the MAPK signaling cascade, may also promote cell proliferation and migration under certain circumstances (37). However, it has been identified that p38MAPK is more active in the process of promoting cell migration, compared with the ERK1/2 signaling cascade (38).…”
Section: Discussionmentioning
confidence: 99%
“…The present study observed that salvianolic acid B suppressed cell proliferation, induced apoptosis and activated cleaved caspase 3 of the osteosarcoma MG63 cell. Wang et al (12) suggested that salvianolic acid B induced apoptosis through p38-mediated ROS generation in human glioma U87 cells and suppressed the growth and angiogenic potential of oral squamous carcinoma cells (20) and neuroblastoma SH-SY5Y cell lines (16).…”
Section: Discussionmentioning
confidence: 99%
“…Water they reduce blood pressure, provide anti-thrombotic activity, expand the blood vessels, increase capillary permeability (12). Clinically, injections of Danshen may expand blood vessels, increase coronary artery blood flow and promote the recovery of ischemic or damaged myocardium, and may treat multiple types of cardiovascular disease (13).…”
Section: Introductionmentioning
confidence: 99%